2022
DOI: 10.1021/acsanm.1c04519
|View full text |Cite
|
Sign up to set email alerts
|

Interlinked Polyaniline/ZnO Nanorod Composite for Selective NO2 Gas Sensing at Room Temperature

Abstract: Chemiresistive gas sensing has attracted extensive research attention in recent years, and the facile low-cost synthesis of sensitive materials is important for realizing practical use. One feasible approach is to create a gas-sensing nanocomposite network by infusing an easily processable conducting polymer into a solution-grown interlinking metal oxide nanomaterial. In this work, a polyaniline (PANi) and ZnO nanorod (NR) composite is synthesized for selective UV-activated NO2 gas sensing at room temperature.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Thus, it occupies the active sites of the pyrrole ring, and therefore, the sensor response decreases. The base resistance of the sensor moderately decreases with increasing relative humidity. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it occupies the active sites of the pyrrole ring, and therefore, the sensor response decreases. The base resistance of the sensor moderately decreases with increasing relative humidity. …”
Section: Resultsmentioning
confidence: 99%
“…Exposure to ethanol increases the base resistance of the sensor, as shown in Figure S8. In considering MP50, a p–n heterojunction is formed by PPy and MnO 2 , resulting in increased electron mobility . The band gap energies of polypyrrole and MnO 2 are 3.8 and 2.3 eV, respectively. , Due to the Fermi energy ( E f ) of MnO 2 differing from that of PPy, electrons in the conduction band of MnO 2 will flow across the interface to the LUMO (lowest unoccupied molecular orbital) of PPy until their Fermi energies equilibrate.…”
Section: Resultsmentioning
confidence: 99%
“…The linear I-V curve indicated that the current conduction is mainly enforced by the bulk sensing material instead of Schottky contacts. 39,40 Different gases have different response characteristics towards a particular material. First, we observed the influence of various gases (CO, C 2 H 5 OH, SO 2 , NO 2 , H 2 S, NH 3 and CO 2 ) on the gas sensing performance of the NFP sensor in prospect of variation in electrical resistance at room temperature ( 27 1C).…”
Section: Gas Sensing Studiesmentioning
confidence: 99%
“…139 Similarly, enhanced host-guest interactions can effectively improve the material's affinity for NH 3 and SO 2 by functionalizing the microporous polymeric framework with carboxylic acid and amidoxime functional groups. 140 Removal of specific contaminant molecules by directional modulation of the chemical composition of the flexible adsorption framework is a straightforward, efficient strategy. For example, polyaniline and its composites exhibit high NO 2 removal efficiency due to the interaction between amino groups and NO 2 molecules.…”
Section: Application Of Flexible Adsorption Materials In Environment ...mentioning
confidence: 99%
“…This was attributed to the strong interaction between OS…Br in the flexible frame and SO 2 and the framework swelling of IUPs during adsorption (Figure 8B). 139 Similarly, enhanced host–guest interactions can effectively improve the material's affinity for NH 3 and SO 2 by functionalizing the microporous polymeric framework with carboxylic acid and amidoxime functional groups 140 …”
Section: Application Of Flexible Adsorption Materialsmentioning
confidence: 99%